2016
DOI: 10.1111/cdev.12619
|View full text |Cite
|
Sign up to set email alerts
|

Birth and Adoptive Parent Antisocial Behavior and Parenting: A Study of Evocative Gene–Environment Correlation

Abstract: Negative parenting is shaped by the genetically-influenced characteristics of children (via evocative rGE) and by parental antisocial behavior, however, it is unclear how these factors jointly impact parenting. The current study examined the effects of birth parent and adoptive parent antisocial behavior on negative parenting. Participants included 546 families within a prospective adoption study. Adoptive parent antisocial behavior emerged as a small but significant predictor of negative parenting at 18 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…In addition, because children share 50% of their genes with each parent, it is difficult to ascertain whether biological parents are more reactive to children’s difficult behavior, due to shared genetically influenced behaviors (i.e., moderated r GE). Adoption studies, being natural experiments, provide complementary opportunities to examine child evocative effects on parenting behavior of genetically unrelated parents (e.g., Klahr et al, 2017). Second, the current study has a relatively small sample size for bivariate behavioral genetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because children share 50% of their genes with each parent, it is difficult to ascertain whether biological parents are more reactive to children’s difficult behavior, due to shared genetically influenced behaviors (i.e., moderated r GE). Adoption studies, being natural experiments, provide complementary opportunities to examine child evocative effects on parenting behavior of genetically unrelated parents (e.g., Klahr et al, 2017). Second, the current study has a relatively small sample size for bivariate behavioral genetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using the same parentoffspring adoption sample as this study indicates prenatal effects (e.g., perinatal internalizing symptoms, prenatal and neonatal complications) on toddlers' behaviors (Marceau, Hajal, et al, 2013;Neiderhiser et al, 2016;Roben et al, 2015), although these studies have mainly focused on toddlers' problem behaviors rather than temperamental characteristics. In addition, previous work has shown evocative rGE effects on parenting during early childhood (e.g., Elam et al, 2014;Fearon et al, 2015;Klahr et al, 2017), although many of these previous investigations did not identify specific child characteristics that mediate the association between heritable influences and parenting. This study aimed to address the gap and extend previous work by simultaneously examining the effects of heritable factors and maternal illicit drug use during pregnancy on child effects on parental negativity via child negative reactivity, while controlling for postnatal rearing environmental influences, using the parent-offspring adoption design.…”
Section: Disentangling Prenatal From Heritable Influences In Explainimentioning
confidence: 97%
“…However, because these are interrelated concepts, and as recommended by previous reviews (e.g., Crandall et al, 2015), I examined maternal intelligence, assessed by a measure of verbal intelligence, as a possible covariate. Lastly, many studies demonstrated that parents experiencing more symptoms of depression, anxiety, or antisocial behaviours also demonstrated more negative parenting behaviours (Klahr et al, 2016;Lovejoy, Graczyk, O'Hare, & Neuman, 2000) and greater EF difficulties (Nigg et al, 2017;Snyder, 2013;Snyder, Miyake, & Hankin, 2015). As a result, maternal psychopathology was examined as a potential covariate.…”
Section: Potential Covariates/confoundsmentioning
confidence: 99%
“…Maternal Psychopathology. I examined maternal psychopathology as a covariate due to research suggesting that it is associated with parenting behaviours, EF and stress (e.g., Klahr et al, 2016;Lovejoy et al, 2000;Nigg et al, 2017). Maternal depression, hostility, and anxiety symptoms were assessed using the Brief Symptom Inventory (BSI; Derogatis, 1993).…”
Section: Self-reported Ef Difficultiesmentioning
confidence: 99%